MENGUKUR KEBERHASILAN EVALUASI PEMBELAJARAN: TELAAH EVALUASI FORMATIF DAN SUMATIF DALAM KURIKULUM MERDEKA DI SD NEGERI 16 BANDA ACEH - Putri Lara Maulida; Cut Oktalisa; Hermalinda; Rahmat Syah Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Implementation in using the independent curriculum, there are two types of evaluation: formative evaluation and summative evaluation. Summative evaluation is carried out at the end of the learning process, academic year, or educational level. Formative evaluation is used to evaluate how well students achieve overall learning objectives. An independent curriculum requires teachers to meet the needs of all students, especially their learning styles. Every student's learning style is different, teachers must be able to facilitate various media, models and innovative learning strategies. In this research, qualitative methods were used, with documents such as books, literature and scientific journals used as secondary data and analyzed through content analysis. The research results define formative assessment as data collected during the learning process and used by educators to make decisions about effective learning activities for their students. Summative assessment is the activity of assessing how well students achieve their learning objectives and/or learning outcomes (CP), which is used as a basis for determining grade promotion and graduation from an educational unit. Formative assessment techniques; Goal Checks, Individual Discussion, Observation, Group Presentation and Self-assessment, while summative assessment techniques; Written test, Portfolio, Performance, and Project. The usefulness of formative and summative assessments is monitoring, identifying, analyzing and improving the learning process, as well as evaluating the achievement of learning objectives for students.